Increasing Understanding of Legal Responsibilities in Ship Accidents (Study at Sinar Bahari Palembang Shipping Vocational School) - Nugraha, Adrian; Syaifuddin, Muhammad; Idris, Akhmad; Dedeng, Dedeng; Al Fansorie, Mahcmod Zakaria (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2023)
This study examines the effectiveness of a community service initiative aimed at enhancing understanding of legal responsibilities in ship accidents among participants from the Sinar Bahari Palembang Shipping Vocational School in Indonesia. Given the dense maritime activity in the region, which exposes vessels to various risks including shipwrecks, groundings, collisions, and fires, a clear comprehension of legal accountability is crucial. The initiative utilized legal counseling sessions incorporating presentations and interactive question-and-answer methods. These sessions engaged 40 participants, including both educators and students, in discussions concerning maritime safety protocols, identification of liable parties in accidents, the role of the National Transportation Safety Commission, and law enforcement measures. Results indicate a significant improvement in participants’ understanding across various key areas. Participants demonstrated heightened awareness regarding maritime security and safety protocols, enabling them to better navigate potential risks. Additionally, they gained clarity on the parties legally responsible for ship accidents, which is essential for ensuring accountability and fair compensation in case of incidents. Moreover, participants acquired insights into the role played by the National Transportation Safety Commission in handling ship accidents, including its investigative and regulatory functions. Understanding these roles helps in facilitating effective accident response and prevention strategies. Furthermore, participants developed a better understanding of the legal enforcement mechanisms applicable to ship accident cases. This knowledge is crucial for ensuring adherence to maritime laws and regulations, thereby promoting safety and accountability within the maritime industry.